1999
DOI: 10.1021/jf9807420
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Salt-Soluble Fraction of Hake (Merluccius merluccius) Fillets Stored at −20 and −30 °C

Abstract: Natural actomyosin (NAM) extracted in 0.6 M NaCl from hake fillets stored at -20 and -30 degrees C for up to 49 weeks was studied. The extracted protein decreased as storage progressed and became poorer in myosin while the proportion of actin remained constant. Two major peaks composed of myosin plus actin and actin plus tropomyosin plus troponins were obtained by size exclusion chromatography. SDS-PAGE analysis of the protein retained in the precolumn filter showed that there was protein aggregated by covalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 27 publications
(39 reference statements)
6
16
3
Order By: Relevance
“…Frozen storage induces denaturation and aggregation of SSPs, which are major contributors to muscle functionality (Del Mazo et al . ). Extracted protein has been used to detect protein changes in frozen fish muscle (Jiménez‐Colmenero et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Frozen storage induces denaturation and aggregation of SSPs, which are major contributors to muscle functionality (Del Mazo et al . ). Extracted protein has been used to detect protein changes in frozen fish muscle (Jiménez‐Colmenero et al .…”
Section: Resultsmentioning
confidence: 97%
“…Consequently, SSPs can be used to measure/monitor changes in proteins when subjected to frozen storage (Del Mazo et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…These high MW proteins possibly resulted from both the pH/NaCl treatments and frozen storage of raw materials. Several studies have demonstrated that protein denaturation during frozen storage resulted in lower extractable proteins, especially myosin, with a decrease in SH groups and an increase in surface hydrophobicity (Owusu‐Ansah and Hultin 1987; LeBlanc and LeBlanc 1992; Del Mazo et al. 1999; Sultanbawa and Li‐Chan 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Proteins in the myofibrillar groups are more susceptible to denaturation than the sarcoplasmic proteins (Sikorski, Olley, & Kostuch, 1976). Most studies have examined the biochemical changes of myofibrillar proteins in frozen stored fish muscles (del Mazo, Torrejón, Careche, & Tejada, 1999;Jiang & Lee, 1985;Tejada et al, 1996), but no research on the alteration of parvalbumin during frozen storage has been reported.…”
Section: Parvalbumin Variation Due To Frozen Storagementioning
confidence: 99%